1997
DOI: 10.1192/s0007125000298711
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects of clinical risk assessment and management

Abstract: It is debatable whether the notion of dangerousness now has any utilitarian value for psychiatry. The presence or absence of dangerousness is very much in the eye of the beholder. It is an all or nothing term – you either have it or you do not! While there is usually little disagreement about the few very violent individuals “who, for 24 hours a day, and in any situation, are likely to cause harm to others” (Chiswick, 1995), most patients are not in this category and “little bit dangerous” is unlikely to be of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Proponents of risk assessment argue that it simply requires basic clinical skills (Snowden, 1997), that the process itself can be valuable (Holloway, 1998), and that it is inseparable from risk management (Kennedy, 2001). Research has identified relevant dispositional, historical and situational risk factors for violence (Monahan & Steadman, 1994), and it has been suggested that actuarial methods might enhance predictive accuracy (Dolan & Doyle, 2000).…”
mentioning
confidence: 99%
“…Proponents of risk assessment argue that it simply requires basic clinical skills (Snowden, 1997), that the process itself can be valuable (Holloway, 1998), and that it is inseparable from risk management (Kennedy, 2001). Research has identified relevant dispositional, historical and situational risk factors for violence (Monahan & Steadman, 1994), and it has been suggested that actuarial methods might enhance predictive accuracy (Dolan & Doyle, 2000).…”
mentioning
confidence: 99%
“…, 1975;Hawton, 1986). Even for an individual, identified risks can increase or decrease over time, and the nature of the risks may change (Snowden, 1997). This has important implications for risk assessment, which may be no more than a 'snapshot' at one particular moment in time.…”
Section: Risk As a Dynamic Conceptmentioning
confidence: 99%
“…On an individual level this might include the risk of suicide, sideeffects from medication, offending behaviour or violence and aggression. Alternatively, we might wish to consider wider outcomes, such as the potential effects on the public or even the risks to the reputation of individual clinicians and the standing of the clinical service (Snowden, 1997).…”
Section: What Is Risk?mentioning
confidence: 99%
See 2 more Smart Citations